ADSORPTION PROPERTIES OF MATERIALS ADSORBING SELECTIVELY ARSENIC FROM AQUEOUS SOLUTIONS CONTAINING MULTIPLE CHEMICAL SPECIES - Yanaka, Ayane; Takeshita, Yuri; Shibata, Keiichiro; Suenaga, Yoshihiro; Yoshida, Hidenori (GEOMATE Journal, 2022)
Arsenic contamination has been confirmed in groundwater around the world. In particular, health hazard by arsenic occurs frequently in developing countries such as Bangladesh. In these countries, it is urgent to remove arsenic from water sources such as groundwater from the viewpoint of the security of safe and sufficient drinking water because population growth is predicted in the future. Especially, inexpensive and simple technology for removing arsenic is required at arsenic-contaminated sites. As a simple method for removing arsenic, the adsorption method is mentioned. However, the adsorption method has two problems. One is that the cost required for the adsorption method is higher than that for other methods, and the other is that it is difficult to adsorb only arsenic selectively when arsenic is mixed with other chemical species. Thus, in this study, the inexpensive adsorbent (improving hydroxyapatite derived from fishbone [Patent No. 6351008 given by Japanese Patent Office], which has a low material cost) to remove arsenic is developed, and the effect of other chemical species on the adsorption performance for the arsenic of the adsorbent is examined. In the case of no chemical species mixing (arsenic only), the case of mixing one or more kinds of chemical species, the adsorption test by the shaking test is carried out, and the adsorption performance is evaluated by the adsorption isotherm. From the test results, it is proven that arsenic is selectively adsorbed, even if the chemical species are mixed.